Changes in visual field of child treated with vigabatrin for 2 years - Mrugacz, Małgorzata; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
We described course of disease of a 12 year old boy with epilepsy, treated with vigabatrin. Pathological changes in visual field in both eyes are reported after 2 years of treatment.